2016
DOI: 10.1542/peds.2016-1730
|View full text |Cite
|
Sign up to set email alerts
|

Parental Refusal of Surgery in an Infant With Tricuspid Atresia

Abstract: We present a case of a fetal diagnosis of tricuspid atresia (TA). The pregnant woman and her husband requested that the baby be treated with only palliative care. The cardiologist did not think it would be appropriate to withhold life-prolonging surgery once the infant was born. The neonatologist argued that outcomes for TA are similar to those for hypoplastic left heart syndrome, and the standard practice at the institution was to allow parents to choose surgery or end-of-life care for those infants. The team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Much of the research into bioethics services are from single-center sites, for example, Gold et al (2011) , Jansen et al (2018) , McDougall and Notini (2016) . Kon et al (2016) describe physicians’ criticism of bioethics for not providing an answer, or not having the right answers in challenging situations. A survey by Bucher et al (2018) , found that nearly half of the health professionals in PICU considered hospital bioethics services to be the “ultimate decision maker,” compared to one tenth who felt that this role should be carried out by the physicians, and just over a third who felt that it was the parents who had the final say.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research into bioethics services are from single-center sites, for example, Gold et al (2011) , Jansen et al (2018) , McDougall and Notini (2016) . Kon et al (2016) describe physicians’ criticism of bioethics for not providing an answer, or not having the right answers in challenging situations. A survey by Bucher et al (2018) , found that nearly half of the health professionals in PICU considered hospital bioethics services to be the “ultimate decision maker,” compared to one tenth who felt that this role should be carried out by the physicians, and just over a third who felt that it was the parents who had the final say.…”
Section: Discussionmentioning
confidence: 99%
“…One way of acknowledging this need for pragmatism is the use of what has been termed the parental zone of discretion ( Lantos, 2018 ). Where a treatment cannot be ethically determined as providing clear benefit, or clear harm, then a pragmatic decision must be made either in terms of the child’s right to treatment, or by following the choices of the parents ( Kon et al, 2016 ). However, in practice, the optimal choice can be difficult to determine, and trust in all those involved is essential.…”
Section: Discussionmentioning
confidence: 99%
“…| 1613 long-term complications associated with a Fontan circulation, some parents prefer end-of-life care at a younger age. 59 In their view, this prevents the prolongation of their child's suffering, however, this remains a highly controversial issue. 59…”
Section: Outcomes After the Fontan Proceduresmentioning
confidence: 99%
“…59 In their view, this prevents the prolongation of their child's suffering, however, this remains a highly controversial issue. 59…”
Section: Outcomes After the Fontan Proceduresmentioning
confidence: 99%
See 1 more Smart Citation